Sur certaines repreÌsentations unitaires d'un groupe infini de transformations - Hove, Leson Van (World Scientific, 2001)
This book brings the rhetorical situation to life. Renowned author and educator Cheryl Glenn translates rhetorical theory into easy-to-follow (and easy-to-teach) techniques that help sharpen students' ability to observe what words, assertions, or opinions might work best with a particular audience in a specific situation.; Translation of the author's thesis (Vrije Universiteit Brussel, 1951) entitled: Sur certaines repreÌsentations unitaires d'un groupe infini de transformations